Application of Sewage Sludge on an Acid Tropical Soil: Crop Response and Heavy Metals Uptake by Maize and Their Accumulation in The Soil - Abdullah, Rosazlin (2002)
At present, Malaysia produces about 5 million m3 sludge per year (wet weight basis). Land application of sewage sludge is considered the most economical and also provides an opportunity to recycle beneficial plant nutrients and organic matter to soil for crop production. However, sewage sludge also contain varying amounts of heavy metals which may pose a hazard of metal toxicity to crops and the consumer of these crops. Thus the uptake of heavy metals by crops and the fate of these heavy metals in soils need to be monitored. The first study, which involved ten sewage sludges, were collected from different wastewater treatment plants and classified into domestic sludge (type A) and light-industry sludge mixed with domestic sludge (type B). The chemical properties of sewage sludge with emphasis on heavy metal content were determined. In general, type B sludge has higher heavy metal content than type A sludge. The concentration of heavy metals in these sludges did not exceed the maximum permitted concentrations (MPC) of the European Community Standard (ECS), for land application, except for Zn (7110.10 mg kg-I). Also, the Cu concentration is rather high in type B sludge. Therefore, type B sludge can be characterized as quite hazardous and unsuitable for agricultural use.